ANALISIS PERDAGANGAN LUAR NEGERI DAN KESEJAHTERAAN NEGARA INDONESIA PADA TAHUN 2019-2021 - Wijayanti, Anggi Karunia; Aprilia, Aprilia; Marpaung, Lilis Aprilia; Alfarisi, Muhammad Farhan; Pratama, Reza Yogi (Fakultas Keguruan dan Ilmu Pendidikan Universitas Jambi, 2023)
This study aims to determine the foreign trade carried out by Indonesia which has a positive and negative impact on the country, as well as find out its effect on the welfare of the country. The data used in this study is secondary data in the 2019-2021 period regarding the total value of oil and gas-non-oil and gas exports and imports and the value of the trade balance. In the data collection process, researchers use data research methods and literature reviews by studying and analyzing the official website of the Central Bureau of Statistics for 2019-2021 as well as looking for information from journals and articles related to the issues raised. From the results of the study, it was found that in 2019, the trade balance declined by 63% in the sense that the trade balance experienced a deficit of 3,230 billion US with a difference of 5,469 billion US from the previous year. Meanwhile, in 2021 the total export value skyrocketed by 41.9% compared to the export value in 2020, resulting in a trade balance surplus of 35,333 or an increase of 62.5% from the value of the trade balance the previous year.